Caffeine intake and pregnancy outcomes: a meta-analytic review - Santos, Ina S.; Victora, Cesar G.; Huttly, Sharon R. A.; Morris, Saul Sutkover (FapUNIFESP, 1998)
Epidemiological publications on the relationship of caffeine to birth weight and duration of human pregnancy, from 1966 to 1995, were searched through Medline. Each study was treated as the stratification variable, and its weight in the weighted average was proportional to the inverse of its variance. Twenty-six studies were located. Among the twenty-two studies on birth weight, eleven were on mean birth weight, nine on low birth weight (LBW), and four on intrauterine growth retardation (IUGR). Combined analysis of mean birth weigh study results showed a significant decrease in birth weight of nearly 43g among newborns of the heaviest caffeine-consuming mothers. LBW, IUGR, and preterm delivery displayed significant homogeneity in the test results, indicating that a pooled estimate should not be taken as an adequate measure. The high heterogeneity of the available literature on the effects of caffeine on LBW, IUGR, and preterm delivery prevents estimation of reliable pooled estimates through meta-analysis. Further assessment of caffeine intake during pregnancy is needed in future research.